KNOWLEDGE AND AWARENESS OF AWARENESS ABOUT INSECTOPHOBIA AMONG DENTAL STUDENTS - A QUESTIONNAIRE SURVEY - Priyanka R, L. Keerthi Sasanka, Dhanraj M. Ganapathy (Drugs and Cell Therapies in Hematology, 2022)
BACKGROUND: Phobia is an intense but unrealistic fear that can interfere with the ability to socialize. Entamophotria / arachnophobia / insectophobia is a correlation between fear of insects & ticks and is considered one of the most serious psychological problems demanding professional treatment. OBJECTIVES: The present study aimed to find the fear of bugs between male and female dental students. MATERIALS AND METHODS: A cross sectional study was conducted among 1st year dental students using a questionnaire that was prepared in google form which was sent electronically to their respective Mail Id’s which is a self structured, pre-validated questionnaire. Statistical analysis was performed in SPSS software version- 23. Pie charts were analysed, chi-square test was done to check the relation of insectophobia among gender. Descriptive and inferential statistics were performed. RESULT: In this survey, 103 responses were gathered, in which 18.45% are females & 17.48% are males who know about Insectophobia and out of which were mostly scared of termites 32.04% totally which is so commonly seen.(p value <0.05) CONCLUSION: Women seem to be more affected by bugs than males in this study. Insectophobia is quite common in this era as most people in this generation are not very close to nature so the identification of whether the insect is poisonous or not is critical. Therapy and counselling needed to be given as termites and other bugs are quite commonly seen in our house. If the phobia prolongs it may even lead to adverse conditions such as loss of life.